2022
DOI: 10.3346/jkms.2022.37.e241
|View full text |Cite
|
Sign up to set email alerts
|

Service Demand for and Awareness of a Primary Healthcare Pilot Project for People With Disabilities

Abstract: Background This study investigated the demand for and awareness of a primary healthcare pilot project for people with disabilities; it also sought to identify relevant determinants for demand and awareness using Andersen’s behavioral model of health service use. Methods This study is a secondary analysis of data from the population-based survey conducted in Gyeonggi Regional Health & Medical Center for People with Disabilities. The data was designed with quota random sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A study investigating the demand for this project reported that having chronic diseases and an unmet need for medical care was significantly related to a higher demand for the project among people with disabilities. 39 When designing a program for people with disabilities, considering the need for home-visiting services can reduce the barriers to care and unnecessary ED visits, which can be an economic burden to the healthcare system. 33 Future studies need to explore the reasons and causes of ED visits among people with disabilities by their different types of disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the demand for this project reported that having chronic diseases and an unmet need for medical care was significantly related to a higher demand for the project among people with disabilities. 39 When designing a program for people with disabilities, considering the need for home-visiting services can reduce the barriers to care and unnecessary ED visits, which can be an economic burden to the healthcare system. 33 Future studies need to explore the reasons and causes of ED visits among people with disabilities by their different types of disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The first HBPC service, launched in May 2018, was a pilot project for the primary care of people with disabilities. Physicians and nurses from the primary clinic completed 2 days of training and visited severely disabled people registered in the National Pension Service to provide medical services [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…More than 90% of patients were dependent in daily living (completely dependent, 42.7%; partially dependent, 49.7%). The overall K-ADL score (median, IQR) was 14 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The most common medical conditions of homebound patients were dementia (27.1%) and difficulty with physical mobility (21.9%).…”
Section: Medical Condition Of Hbpc Users By Type Of Servicementioning
confidence: 99%
See 2 more Smart Citations